CLINICAL AND MORPHOLOGICAL CHANGES OF THE ORAL MUCOSA IN ERYTHEMA MULTIFORME (Multidisciplinary Journal of Science and Technology, 2026)
The article presents the results of a study of the clinical course and cytomorphological features of the oral mucosa in 42 patients with erythema multiforme (EM) in the Bukhara region. The authors identified three groups of patients according to the severity: mild, moderate, and severe (Stevens-Johnson syndrome). It was established that the dynamics of the cellular composition (neutrophils, polyblasts) directly depends on the severity of the pathology and the presence of chronic foci of infection.